Determinants of stunting among children under five years: A systematic review - Fatmalina Febry; Hasyim Kadri; Trisnawarman Trisnawarman; Icon Harizon; Muhammad Hasan Azhari; Adinda Syafhira (School of Health Sciences Al-Ma'arif, 2026)
Background: Stunting remains a major chronic nutritional problem among children under five years and reflects long-term growth failure caused by biological, maternal, socioeconomic, environmental, and child-related determinants. Although many observational studies have examined factors associated with stunting, the evidence remains dispersed across different countries, populations, and methodological designs. A systematic synthesis is therefore needed to identify recurring determinants and clarify the strength of available evidence. Objective: This systematic review aimed to identify and synthesize determinants associated with stunting among children under five years of age based on recent observational studies. Methods: A systematic review was conducted following the PRISMA 2020 reporting guideline. Literature searches were performed in PubMed, ScienceDirect, and Google Scholar for articles published between 2021 and 2026. The search combined keywords and Boolean operators related to stunting, determinants, risk factors, associated factors, and children under five. 15 studies were included in the final synthesis. Study quality was assessed using the Joanna Briggs Institute critical appraisal tools. Data were synthesized narratively and grouped into maternal, socioeconomic, environmental, and child-related determinants. Results: The most consistently reported determinants were low maternal education, poor maternal nutritional status, short maternal stature, low household income, household food insecurity, poor sanitation, limited access to clean water, low birth weight, lack of exclusive breastfeeding, and inadequate complementary feeding practices. Most included studies demonstrated moderate methodological quality, although limitations remained in confounding control, sampling procedures, and causal interpretation. Conclusion: Stunting among children under five is associated with recurring and interrelated determinants across multiple domains. Because most studies were observational and meta-analysis was not performed, findings should be interpreted as recurring associations rather than definitive causal evidence. Future longitudinal and intervention studies are needed.